2017
DOI: 10.1089/scd.2016.0320
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Profiling of Partial and Fully Reprogrammed Induced Pluripotent Stem Cells

Abstract: Acquisition of proper metabolomic fate is required to convert somatic cells toward fully reprogrammed pluripotent stem cells. The majority of induced pluripotent stem cells (iPSCs) are partially reprogrammed and have a transcriptome different from that of the pluripotent stem cells. The metabolomic profile and mitochondrial metabolic functions required to achieve full reprogramming of somatic cells to iPSC status have not yet been elucidated. Clarification of the metabolites underlying reprogramming mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Additional metabolic analyses, and the inclusion of additional lines, would further elucidate the extent of metabolic memory retention by iPS cells. Recently, Park et al [ 51 ] reported significant differences in mitochondrial activity and specific metabolite levels in partially reprogrammed iPS cells, relative to fully reprogrammed iPS cells. In addition, Prigione et al [ 19 ] documented the acquisition of mtDNA mutations in human iPS cell lines not present in the parental cell line following reprogramming, while mouse iPS cells show altered mitochondrial replication upon differentiation relative to ES cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional metabolic analyses, and the inclusion of additional lines, would further elucidate the extent of metabolic memory retention by iPS cells. Recently, Park et al [ 51 ] reported significant differences in mitochondrial activity and specific metabolite levels in partially reprogrammed iPS cells, relative to fully reprogrammed iPS cells. In addition, Prigione et al [ 19 ] documented the acquisition of mtDNA mutations in human iPS cell lines not present in the parental cell line following reprogramming, while mouse iPS cells show altered mitochondrial replication upon differentiation relative to ES cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these differences exist, their functional impact on maintenance of pluripotency or differentiation capacity have not been examined. Partially reprogrammed cells, which are characterized by forming stable ESC-like colonies but not expressing endogenous OCT4, NANOG, SSEA4 and TRA-1-60, appear to have a distinct mitochondria and metabolic profile that are intermediate between fully reprogrammed iPSCs/ESCs and parental fibroblasts in terms of mitochondrial morphology and gene expression, and concentrations of glycolytic and OxPhos intermediates (Lee et al, 2016;Park et al, 2017). This insufficient repression of mitochondrial function and activation of glycolysis in partially reprogrammed cells can be rescued through microRNA 31 overexpression, which suppresses succinate dehydrogenase A activity to promote the transition from OxPhos to glycolysis and enhance reprogramming efficiency (Lee et al, 2016).…”
Section: Energy Metabolism Drives Acquisition Of Pluripotency Throughmentioning
confidence: 99%
“…2,47,48 In humans, partially reprogrammed iPSCs resumed reprogramming by upregulation of KLF4, 49 and pre-iPSC-like cell lines were established as cancer stem cell lines. 50 Metabolome profiling demonstrated that human partially reprogrammed iPSCs shared only 74% similarly expressed metabolites with human ESCs, 51 indicating that transcriptome of partially reprogrammed stem cells is considerably different from that of ESCs. Therefore, establishment of iPSC lines makes no promise to establish stable lines of human partially reprogrammed iPSCs.…”
Section: Mechanisms Of Reprogramming In Humansmentioning
confidence: 99%